2015
DOI: 10.1186/s40659-015-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer DNA methylation patterns from patients in Manaus, Brazil

Abstract: BackgroundDNA methylation is commonly linked with the silencing of the gene expression for many tumor suppressor genes. As such, determining DNA methylation patterns should aid, in times to come, in the diagnosis and personal treatment for various types of cancers. Here, we analyzed the methylation pattern from five colorectal cancer patients from the Amazon state in Brazil for four tumor suppressor genes, viz.: DAPK, CDH1, CDKN2A, and TIMP2 by employing a polymerase chain reaction (PCR) specific to methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Specifically, CDH1 , which encodes the cell adhesion protein E-cadherin, is an important TSG 55. Studies have shown that loss of CDH1 expression by promoter hypermethylation is involved in several types of cancer, including colorectal,56 lung,57 breast,23 and gastric cancers 58. This meta-analysis was done to resolve some of the inconsistent reports of the association between CDH1 promoter methylation and HNSCC 15,16…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CDH1 , which encodes the cell adhesion protein E-cadherin, is an important TSG 55. Studies have shown that loss of CDH1 expression by promoter hypermethylation is involved in several types of cancer, including colorectal,56 lung,57 breast,23 and gastric cancers 58. This meta-analysis was done to resolve some of the inconsistent reports of the association between CDH1 promoter methylation and HNSCC 15,16…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, an understanding of the underlying molecular mechanisms that play a major role in DAPk1's transcriptional regulation constitutes a prerequisite to the development of novel therapeutics against cancer and inflammation-associated diseases [175]. Strikingly enough, a detailed analysis of the mRNA and protein expression profile of DAPk1 in various tumor cell lines, including bladder, breast and renal carcinomas, led to the discovery of loss of DAPk1 expression [176].…”
Section: Death-associated Protein Kinasementioning
confidence: 99%
“…It is expected that an understanding of the underlying molecular mechanisms regulating members of the DAPk family or triggering their associated death responses is essential to the development of DAPk based therapies to combat cancer and associated diseases [ 34 ]. As described earlier, DAPk1 and DAPk2 can be activated by several mechanisms, including binding of Ca 2+ -activated CaM, which allows the release of the catalytic domain from inhibition by the CaM autoregulatory domain, phosphorylation of ERK, and dephosphorylation of Ser308 [ 27 ].…”
Section: Dapk1 and Dapk2: Regulation And Signaling Pathwaymentioning
confidence: 99%